The Prevalence of Microalbuminuria in Type 2 Diabetes Mellitus Patients in Ilanur Mother and Child Hospital Tangerang - Ahmad Yani; Rizka Lestari Widhayanti; Budi Siswanto (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2023)
Type 2 diabetes mellitus (DMT2) is still a global health problem. If not treated properly, DMT2 can lead to chronic conditions such as albuminuria, a condition in which albumin is found in the urine due to decreased kidney function. The presence of elevated albumin levels in the form of microalbuminuria indicates that DMT2 disease has progressed. This study aims to describe the prevalence of microalbuminuria in DMT2 patients who have urine microalbumin examined at RSIA Ilanur, Tangerang City. This type of research is descriptive, with a cross-sectional approach and a total of 28 respondents. The method used to examine microalbuminuria is fluorescence immunoassay using the Boditech AFIAS instrument. The urine microalbumin profile obtained was then analyzed based on gender, age, and duration of suffering from DMT2. Based on the research, it can be concluded that the majority of DMT2-sufferers are women. The age range of most sufferers is in the age group of 51–60 years. Meanwhile, based on the duration of suffering from DMT2, the categories <5 years and ≥5 years both have a 50% frequency distribution. Based on the microalbuminuria examination profile, both male and female groups showed a proportion of 75% microalbuminuria incidence. The number of DMT2 sufferers who experienced microalbuminuria was higher in the age group of 51–60 years (73.3%). Meanwhile, based on the duration of suffering from DMT2, the group of respondents <5 years tended to have higher cases of microalbuminuria (78.6%) in the population studied.